Existence of an additional layer in equatorial ionosphere: Other observations - Zain, A.F.M; Abdullah, S; Abdullah, M; Homam, M.J; Ho, Yih Hwa (2006)
In this paper we present an observation of an additional layer over the Malaysian ionosphere using bottomside sounding. This F3 layer has been observed over Brazil by Balan et al. (1995). Other work done by Uemoto et al. (2004) from the observation of topside sounding obtained by the Ohzora satellite confirmed this work. In Malaysia, the layer has been observed at the newly established ionosonde station at Batu Pahat (lat. 1° 86′ N, long. 103° 8′ E). This station has been in operation since October 2004. Continuous sweep soundings are made every 15 minutes along with single frequency soundings. Greatest appearance of the F3-layer is around local noon while the least is after local dawn. The mean height for the layer is about 600 km reaching a maximum of about 900 km during the months of Nov, 2004 – Jan, 2005. This period is in agreement with the occurrence of F3 layer observed by Balan et al. work (December solstices). It is seen that the critical frequency of the F2 layer decreases with the appearance of the F3-layer. This phenomena can be attributed to the equatorial anomaly and the upward neutral wind and E x B drift.